Does geographical location matter for ethnic wage gaps?. (30th September 2019) - Longhi, Simonetta
Abstract: This paper analyzes ethnic wage gaps in Great Britain by comparing minorities to majority workers in the same local labor market and focuses on the variation of wage gaps across areas. As wage gaps vary across areas, using one single national measure may be misleading. Higher wage gaps across groups are associated with higher occupational segregation and ethnic diversity, while higher wage gaps within groups are associated with higher regional specialization and proportion of co‐ethnics. Policies could help by improving job location and selection into occupations across groups.